Analisa Korelasi Protokol Kesehatan Covid 19 Terhadap Keputusan Pembelian Di Kedai Kopi Kiko, Jakarta - Candra Hidayat (Jurnal Sains Terapan Pariwisata, 2021)
COVID-19 is currently taking the world by storm. WHO itself has even designated this virus as a world pandemic. In early 2020, Indonesia contracted Covid 19 and specifically in DKI Jakarta. DKI Jakarta is the province with the largest number of cases exposed to the corona virus in Indonesia, with a total of 28,882 cases. The Indonesian government through the Ministry of Health has issued a Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07 / menkes / 382/2020 regarding health protocols for the public in public places and facilities in the context of prevention and control of the 2019 corona virus disease (covid-19). This study was to determine the effect of health protocols on purchasing decisions at the Kiko Coffee Shop. This research method uses a descriptive approach. The overall results of this study are for the level of influence of health protocols on purchasing decisions at Kiko Coffee Shops. The average statistic is 4.6331 and the standard deviation is 0.36381. And for the purchasing decision level at the Kiko Coffee Shop. The average statistic is 4.5810 and the standard deviation is 0.44860. There is a strong relationship between health protocols and purchasing decisions at the Kiko Coffee Shop, with a value of r = .840. With the existence of a health protocol and this is a factor in increasing purchasing decisions from visitors at Kiko Coffee Shop. Suggestions for management to promote more to the female market segment.